Comparative evaluation of HbA1c in point-of-care testing (POCT) devices: enzymatic and immunoassay methods compared to ion-exchange high-performance liquid chromatography (IE-HPLC) - Windradini Rahvian Aridama; Ferdy Royland Marpaung; Yessy Puspitasari (Medicinski glasnik, 2026)
Aim: To evaluate 3 point-of-care testing (POCT) devices in testing HbA1c: the Simplex TAS TM 101 (Tascom Co. Ltd., South Korea), which utilizes an enzymatic method, and two immunoassay-based devices, the Zybio Q8 Pro and Zybio EXR 110 (Zybio Inc., China). Methods: A total of 40 whole blood samples with EDTA anticoagulant were collected patients undergoing HbA1c testing at the outpatient department. The samples were analyzed using 3 POCT devices and one reference method. Results: Passing-Bablok regression revealed no significant fixed or proportional bias. Strong correlations with the gold standard were observed for Simplex TAS TM 101 (r=0.944), Zybio Q8 Pro (r=0.910), and Zybio EXR 110 (r=0.839), all with p<0.001. Bland-Altman analysis confirmed that the majority of measurements fell within an acceptable clinical range. Conclusion: This study demonstrated that the three POCT devices employing enzymatic and immunoassay methods served as reliable alternatives to ion exchange-high-performance liquid chromatography (IE-HPLC) for HbA1c measurement in clinical practice.
Keywords: diabetes; laboratory; point-of-care testing